Seasonal Changes of Nutrient Concentrations in Water of Some Locations in Southern Iraqi Marshes, After Restoration. (Baghdad Science Journal, 2025)
After restoration of Iraqi marshes during 2003, three locations were chosen, one in each main marsh (Um Al-Naaj site in Al-Hwaizeh marsh; Al-Nagarah site in Al-Hammar marsh and Al-Baghdadia site in Al-Chebaysh marsh) to determine the concentrations of nutrients (Nitrate, Nitrite, Phosphate and Silicate) in water seasonally for the period winter, spring, summer, and autumn at 2007. Five water replicates were collected from each site, seasonally. In the Lab., the samples were analyzed by colorimetric methods; the results showed that Um-Al-Naaj site has the highest nutrients level, while Al-Nagarah site has the lowest level. The statistical program t-test was applied at the significant levels (P-value < 0.01) and (P-value < 0.05) to know the significant differences in the nutrients concentration among the sites, as well as among the seasons. Statistically, the results showed that NO3, NO2, and PO4 concentrations have significant differences among the sites, as well as among the seasons. While, SiO2 concentrations have no significant differences among the sites, but they differed significantly among the seasons.